Islam dan Identitas Lokal di Desa Gonting Malaha, Kabupaten Asahan: Studi Sosial-Historis Abad ke-20 - Samosir, Nuri Helga Akhiriyah; Tanjung, Muaz (Local History & Heritage, 2025)
This study aims to analyze the role of Islam in shaping the local identity of the Gonting Malaha community and to identify the influencing factors Employing a qualitative method with a diachronic historical approach, this research utilizes Miles and Huberman’s interactive data analysis model, encompassing data reduction, data display, and repeated verification until saturation is achieved. The results indicate that Islam plays a vital role not only as a religious belief but also as the foundation for moral values, ethical norms, and the formation of social identity in the village. Structured religious education, solidarity-based social values, and the integration of local culture are central to the internalization of Islamic principles within daily community life. Moreover, Islam contributes to fostering interreligious harmony and encourages active participation in social activities. These findings underscore the significance of understanding the interplay between social history and Islamic influence in Gonting Malaha, which is essential for preserving local cultural heritage and strengthening interfaith tolerance in contemporary Indonesian society.